Characterization of charge transfer mechanisms in the molecular capacitor β-DiCC[Ni(dmit)2] using TD-DFT methods (2017)
This study describes the charge transfer mechanisms in the redox equilibrium of the molecular capacitor β-DiCC[Ni(dmit)2] by means of the DFT approach. Calculations on the DiCC and [Ni(dmit)2] fragments show that the ionic form β-DiCC+[Ni(dmit)2]- is more stable than the neutral form β-DiCC0[Ni(dmit)2]0 by 6.27 kcal/mol, in agreement with a spontaneously reversible redox (charge transfer) process, as proposed from the experiments. Time Dependent DFT calculations have been also performed for the excited states searching. A doublet excited state D8, at 40.7 kcal/mol, has been found to be consistent with a photoinduced mechanism for the redox equilibrium within β-DiCC[Ni(dmit)2]. A detailed description of the transitions, electronic structure, and charge transfer is also presented.